2017
DOI: 10.1016/j.epsl.2017.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of strain localization in heterogeneous, polycrystalline rocks – a numerical perspective

Abstract: including the URL of the record and the reason for the withdrawal request. Highlights  Shear zones are difficult to form without a dynamic weakening mechanism  Dynamic weakening can quickly localize strain into an interconnected weak zone  Competing weakening and strengthening processes impact shear zone pattern  Shear zones are dynamic in time and space within a single deformation event  Finite strain patterns do not fully represent the evolution of a shear zone network *Highlights (for review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
(87 reference statements)
3
32
0
Order By: Relevance
“…In an attempt to model rock weakening and strain localization, different types of softening parameterizations have been previously used in order to describe the weakening behavior of natural materials. For example, Gardner et al () studied strain localization using different load bearing framework geometries. They found that interconnected weak layers are hard to form without a dynamic weakening process, which was also observed in an experimental study by Holyoke and Tullis ().…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to model rock weakening and strain localization, different types of softening parameterizations have been previously used in order to describe the weakening behavior of natural materials. For example, Gardner et al () studied strain localization using different load bearing framework geometries. They found that interconnected weak layers are hard to form without a dynamic weakening process, which was also observed in an experimental study by Holyoke and Tullis ().…”
Section: Discussionmentioning
confidence: 99%
“…This implies the necessity of using softening laws to properly model strain localization and thus shear zone formation. Gardner et al () used a different implementation to simulate weakening. They introduced stress dependent softening combined with time dependent hardening focusing on the transition from nonlinear to linear flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1020 Ma. Given the uncertainty of the dating, as well as other observations about the temporal and spatial pattern of strain localization (e.g., Jessell et al, 2005;Gardner et al, 2017), the shear zones on the eastern and western margins of the granite need not have formed synchronously.…”
Section: Geologic Context For Strain Localizationmentioning
confidence: 99%
“…Previous studies have shown that connectivity and continuity of phases play a significant role in Journal of Geophysical Research: Solid Earth 10.1002/2017JB014000 the constitutive behavior of rocks [Burg and Wilson, 1987;Jordan, 1988;Handy, 1990;Bloomfield and Covey-Crump, 1993;Handy, 1994]. In addition, transitioning from a strong-phase supported framework (i.e., quartz dispersed around stronger feldspar grains that support the load) to a weak-phase supported network (i.e., weak interconnected quartz layers support the load) dramatically reduces a rock's bulk strength [Arzi, 1978;Nicolas, 1992;Gardner et al, 2017]. In the case of the Seven Gables outcrop, it appears that the dike's composition facilitated the development of monomineralic quartz layers, which led to weakening compared to the granodiorite.…”
Section: Strength Contrast Between Granodiorite and Dikementioning
confidence: 99%